2018
DOI: 10.1002/jclp.22597
|View full text |Cite
|
Sign up to set email alerts
|

The effect of positive and negative memory bias on anxiety and depression symptoms among adolescents

Abstract: Therapeutic strategies to increase positive memory bias may reduce anxiety symptoms only among those with high depression scores. Interventions to reduce negative memory bias may reduce anxiety symptoms irrespective of levels of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Another study of emotional encoding found that individuals with high anxiety preferentially encode negative contexts (Lee & Fernandes, 2017). Bias toward negative memory is correlated with anxiety in adolescents, while stronger emotional memory is also observed in adolescents with particular depressive disorders (Ho, Cheng, Dai, Tam, & Hui, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Another study of emotional encoding found that individuals with high anxiety preferentially encode negative contexts (Lee & Fernandes, 2017). Bias toward negative memory is correlated with anxiety in adolescents, while stronger emotional memory is also observed in adolescents with particular depressive disorders (Ho, Cheng, Dai, Tam, & Hui, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Using a modified Sternberg task, Yoon et al [24] observed depression-related deficits in inhibiting irrelevant emotional materials, both positive and negative; no such effect was found for anxiety, suggesting a depression-specific deficit in updating emotional contents in WM. However, a study of memory control in healthy adolescents observed a reverse pattern: anxiety was associated with difficulties forgetting negative words, whereas depression was not [32].…”
Section: Introductionmentioning
confidence: 97%
“…Numerous studies have shown that recall or recognition of depression-related materials in depressed individuals has a relatively obvious bias [1][2][3], which is called the negative moodcongruent effect [4][5][6]. These cognitive biases in depressed individuals may lead to the onset or deepening of depression [3,7].…”
Section: Introductionmentioning
confidence: 99%